Catholic Social Teaching and Economics: Reflections on the Economy of Francesco - Beretta, Simona (The review of faith & international affairs, 2023)
The paper describes the impact of the Economy of Francesco (EoF) on the economic debate and practices, within the framework of the Catholic Social Teaching. EoF was a cultural and experiential process and event held online and through a number of meetings around the world between March 2020 and September 2022. The anthropological limitations of homo economicus, with his methodological egoism and procedural rationality, and the need for a broad approach to education are discussed. The paper highlights strengths and weaknesses of EoF and reviews what has been already accomplished in the process and what is still to be accomplished.